2011
DOI: 10.4048/jbc.2011.14.3.204
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Significance of the Lymph Node Ratio in Axillary Lymph Node Positive Breast Cancer

Abstract: PurposeThis study evaluated the prognostic impact of the lymph node ratio (LNR; i.e., the ratio of positive to dissected lymph nodes) on recurrence and survival in breast cancer patients with positive axillary lymph nodes (LNs).MethodsThe study cohort was comprised of 330 breast cancer patients with positive axillary nodes who received postoperative radiotherapy between 1987 and 2004. Ten-year Kaplan-Meier locoregional failure, distant metastasis, disease-free survival (DFS) and disease-specific survival (DSS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 26 publications
1
17
0
1
Order By: Relevance
“…Our retrospective analysis of 236 patients who received NAC revealed that LNR was a more significant prognostic factor than nodal stage. Previous studies that mostly reported patients who did not undergo NAC demonstrated the oncologic importance of the LNR as a predictor of prognosis in breast cancer [5–7]. Only a few studies have focused on patients who received NAC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our retrospective analysis of 236 patients who received NAC revealed that LNR was a more significant prognostic factor than nodal stage. Previous studies that mostly reported patients who did not undergo NAC demonstrated the oncologic importance of the LNR as a predictor of prognosis in breast cancer [5–7]. Only a few studies have focused on patients who received NAC.…”
Section: Discussionmentioning
confidence: 99%
“…The extent of axillary dissection varies according to the surgeon and there is further variation in the number of reported positive nodes across different pathology laboratories [4]. More extensive axillary dissection or pathologic examination of the resected specimen results in a higher number of positive nodes [5]. Recent studies have reported the oncologic importance of the lymph node ratio (LNR), defined as the ratio of involved nodes to dissected nodes, as a predictor of prognosis in breast cancer [5–8].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the number-based staging system, the LNR classification model exploits additional information on the total number of lymph nodes removed. Increasing evidence is establishing the prognostic role of the LNR in breast cancer [ 10 , 18 – 21 ]. Our results support previous findings, demonstrating that the LNR is a prognostic factor in both multivariate and univariate analyses.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis is similar compared with carcinoma of the anatomic breast with the same tumor stage and histology, although ectopic axillary breast carcinoma has a higher rate of lymph node involvement, 4,6,11 which is a known important prognostic factor for overall survival. 13,14…”
Section: Discussionmentioning
confidence: 99%